LINGUISTIC-COGNITIVE ANALYSIS OF THE CONCEPT FATHER - Khayitova Shohida Erkin Kizi (Journal of new century innovations, 2024)
Annotation. This article is written about the concept of “Father” uzbek languages from linguistic-cognitive approach. The significance and role of the father concept in linguistic and cultural studies, its pragmatic aspects, and its status in some works are highlighted on the basis of factual examples.